Phytic acid layer template-assisted deposition of TiO2 film on titanium: Surface electronic properties, super-hydrophilicity and bending strength. (5th January 2016) - Zhang, Xuan; Chen, Yingqi; Lei, Huili; Zhao, Sheng; Han, Fei; Xiang, Xia; Zhao, Yuancong; Huang, Nan; Wan, Guojiang
Abstract: Titanium dioxide film has received a great deal of attention, because of its excellent potentials and implications, in a variety of fields. Practically, the film is required to be well mechanically blended with the substrate (e.g. good compliance or flexibility) together with its surface properties to accomplish multiple functions. In this work, phytic acid (PA) layer template-assisted deposition of thin TiO2 film was implemented on titanium substrate to produce a good combination of surface properties and bending strength. Relatively smooth, homogenous and thin (ca. 800 nm) anatase TiO2 films were obtained on the PA pre-templated Ti substrate. Significantly enhanced photoluminescence was observed on the PA template-deposited TiO2 as compared to the direct deposited TiO2 . This is correlated with its higher carrier density in the space charge layer as disclosed by the Mott–Schottky investigation. Likewise, the prepared TiO2 films are super-hydrophilic (with water contact angle less than 5°), which is credited to the higher polar contribution of surface energy. Moreover, the PA template-deposited TiO2 film withstood plastic deformation up to 180° angle bending without failure. This template-assisted deposition of TiO2 film via surface-immobilized organic layer on rigid substrate suggests a promising route to enhance both its mechanical and physical performances. Graphical abstract: Highlights: Phytic acid layer template-assisted deposition of TiO2 film was executed on Ti. Enhanced Photoluminescence was obtained on the PA template deposited TiO2 . The prepared TiO2 film exhibited super-hydrophilic with contact angle less than 5°. The template-assisted deposited film demonstrated excellent bending strength on Ti. A good combination of mechanical compliance and physical functionalities achieved.